PLANEJAMENTO ESTRATÉTICO E CITY MARKETING: A NOVA FACE DAS CIDADES NO FINAL DO SÉCULO XX - Pinto, Georges José (Caminhos de Geografia, 2001)
The objectives of the world big cities directors and owners of business entreprisesat the end of the XX Century are: to produce the city's image, to foment its products and services, to project it in a globalizated world, to attract resources. The are the aims that have to be obtained in the beginning of the XXI Century. And how to get them? Using two ways: the strategic planning and the city marketing.